2017
DOI: 10.1007/s11244-017-0812-2
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Ni/γ-Al2O3 Catalysts in CO Methanation: Effect of Zr, Mg, Ba and Ca Oxide Promoters

Abstract: reserves [1,2]. The SNG production process involves two steps: gasification of the carbon-containing feedstock and subsequent catalytic methanation of the resulting synthesis gas. Methanation of synthesis gas involves the two following reactions [3][4][5]:These reactions are thermodynamically favored at low temperature and high pressure [6]. It is therefore that the methanation process is designed to effectively remove the heat of reaction and thus maximize the methane yield [1,7]. There are currently two main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…222 However, rapid coke deposition on the catalyst surfaces during the reaction limits the practical use of Ni-based catalysts. 217,223 To cope with such challenges, noble metals like Rh Ru, Pt, Ir, and Pd were also investigated, because of their higher coking resistance. [224][225][226] Good catalyst performances and resistance to deactivation by coking were showed by supported bimetallic catalysts such as Ni-Rh/LaAlO 3 , 227 Ni-Cu/MgO, 228 and Ni-Mn/Al 2 O 3 .…”
Section: Dry Reforming Of Methane (Drm)mentioning
confidence: 99%
See 2 more Smart Citations
“…222 However, rapid coke deposition on the catalyst surfaces during the reaction limits the practical use of Ni-based catalysts. 217,223 To cope with such challenges, noble metals like Rh Ru, Pt, Ir, and Pd were also investigated, because of their higher coking resistance. [224][225][226] Good catalyst performances and resistance to deactivation by coking were showed by supported bimetallic catalysts such as Ni-Rh/LaAlO 3 , 227 Ni-Cu/MgO, 228 and Ni-Mn/Al 2 O 3 .…”
Section: Dry Reforming Of Methane (Drm)mentioning
confidence: 99%
“…A linear correlation was observed between the amount of carbon formed and the degree of deactivation of the catalyst. 216 Barrientos et al 217 investigated various Ni/Al 2 O 3 catalysts promoted with MgO, CaO, BaO, and ZrO 2 under low-temperature conditions (300 °C), and they showed that the presence of Zn lowers the formation of polymeric carbon. Galhardo et al , 92 with in situ spectroscopic analyses, observed that the accumulation of carbon species on the surface of a Ni/SiO 2 catalyst at high temperatures leads to a Ni 3 C-like phase, which changes the process selectivity towards the formation of CO. After carbon depletion from the surface of the Ni particles by oxidation, the catalyst regains its high selectivity to CH 4 production.…”
Section: Materials and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopants are typically metal oxides such as Zr, Ce, La, V and Mg. The addition of zirconia to catalyst materials reduces the carbon formation and the activity deactivation due to sintering [570]. Ceria remarkably prevents the formation of coke deposits and improves the catalytic activity and stability [571].…”
Section: Catalytic Methanationmentioning
confidence: 99%
“…They found that the dissociation of CO2 led to minor formation of RhOx is the reason for the enhanced activity in Rh/Al2O3 catalyst. But, it is noteworthy that the existing metal promoters still suffered from deactivation because of low surface area of support material and low dispersion of loaded metal, which can be avoidable by choosing a suitable supported metal material [20].…”
Section: H2 + Co → Ch4 + H2omentioning
confidence: 99%